Clinical outcomes of conversion surgery following neoadjuvant chemoimmunotherapy in potentially resectable stage IIIA/IIIB non-small cell lung - Yana Qi; Yulan Sun; Yanran Hu; Hui Zhu; Hongbo Guo (Scientific Reports)
Abstract Neoadjuvant chemoimmunotherapy has been successfully used in patients with resectable non-small-cell lung cancer (NSCLC). However, its application to potentially resectable IIIA/IIIB NSCLC remains controversial. This retrospective study aims to evaluate the efficacy and safety of neoadjuvant chemoimmunotherapy followed by conversion surgery in patients with potentially resectable stage III NSCLC, focusing on conversion rate and survival benefits. Patients with ‘potentially resectable’ stage IIIA/IIIB NSCLC who were deemed unsuitable for complete (R0) resection at initial diagnosis were retrospectively identified. After 2–4 cycles of treatment, all patients were reevaluated for surgical resectability. Data on patient characteristics, radiological and pathological responses, and survival outcomes were collected. In total, 148 patients were included in the final analysis. Upon the completion of neoadjuvant therapy, 105 patients were considered suitable for conversion surgery. Three patients refused surgery, and 102 patients ultimately underwent surgery, yielding a conversion rate of 70.9% and a resection rate of 68.9%. The rate of complete (R0) resection was 100%, with a major pathological response (MPR) of 64.7% and a pathologic complete response (pCR) of 41.2%. Postoperative complications were observed in nine patients (8.8%), and there was no surgery-related mortality within 30 days. The median progression-free survival (PFS) was 19.1 months in the non-surgery group, and the overall survival (OS) was not reached. In the 102 patients who underwent conversion surgery, both the median PFS and OS were not reached, accompanied by 2-year OS and PFS rates of 87.3% and 78.4%, respectively. Our findings showed that neoadjuvant chemoimmunotherapy expanded the opportunities for conversion surgery in potentially resectable cases. Subsequent conversion surgery is safe and has the potential for significant survival benefits.